A multiobjective optimization procedure for the electrode design of cochlear implants. (17th May 2018) - Ramos‐de‐Miguel, Ángel; Escobar, José M.; Greiner, David; Ramos‐Macías, Ángel
Abstract: This paper presents a new procedure to design optimal electrodes for cochlear implants. The main objective of this study is to find a set of electrode designs that maximize the focalization and minimize the power consumption simultaneously. To achieve that, a criterion to measure the ability of focalization of an electrode is proposed. It is presented a procedure to determine (1) the electrical potential induced by an electrode by solving the Laplace equation through the finite element method; (2) the response of a neuron to an applied field using NEURON, a compartmentalized cell model; (3) the optimization to find the best electrode designs according to power consumption and focalization by 2 evolutionary multiobjective methods based on the non‐dominated sorting genetic algorithm II: a straight multiobjective approach and a seeded multiobjective approach. An electrode design formed by 2 conductive rings with a possible difference of potential between them is proposed. It is analyzed that the response of the neuron is determined by the shape and the difference of the potential between the electrode rings. Our procedure successfully achieves a nondominated set of optimum electrode designs improving a standard electrode in both objectives, as designs with better focalization allow to include extra electrodes in the cochlear implant, and designs with lower power consumption extend the length of the battery. Abstract : This article proposes a methodology, numerical framework, implementation, and new evaluation functions to automatically design cochlear implant electrodes. The design is focused on focalization of the stimulus on a narrow area of the auditory nerve and power saving. The novelty of this work is the focalization measurements based on a simulated nerve and the proposed optimum designs. Moreover, we have studied simplified designs both in terms of voltage and shape achieving electrodes easy to build and keeping the current electronics without a considerable detriment in global performance.